A brief history of justice - Johnston, David 1951- (Chichester, West Sussex Malden, MA Wiley-Blackwell, 2011)
"A Brief History of Justice traces the development of the idea of justice from the ancient world until the present day, with special attention to the emergence of the modern idea of social justice. An accessible introduction to the history of ideas about justice Shows how complex ideas are anchored in ordinary intuitions about justice Traces the emergence of the idea of social justice Identifies connections as well as differences between distributive and corrective justice Offers accessible, concise introductions to the thought of several leading figures and schools of thought in the history of philosophy "-- Provided by publisher.
"The idea of justice has been central to political philosophy since its origin. Indeed, the two towering book-ends to Western political thought -- Plato's Republic and John Rawls' milestone 1971 publication, A Theory of Justice-- are both essays on justice. Structured around the historical and conceptual relationship between distributive and corrective justice, A Brief History of Justice traces the development of this fundamental idea from antiquity to the present day. This wide-ranging, yet concise book delves deeply into the evolving traditions of justice, from roots in Babylonian and Hebrew law and Greek political thought to the most prominent contemporary renderings in the work of Rawls and other modern thinkers, including incisive chapter-length introductions to the work of Plato, Aristotle, the utilitarians, Kant, and Rawls. David Johnston weaves a sophisticated, yet accessible, narrative, integrating philosophical discussion with pressing contemporary questions about justice. With clarity and scholarly precision, A Brief History of Justice offers readers an invaluable survey of an important and powerful concept that continues to dominate the field of political philosophy"-- Provided by publisher.
Machine generated contents note: Introduction. -- Prologue: From the Standard Model to a Sense of Justice. -- 1: The Terrain of Justice. -- 2: Teleology and Tutelage in Plato's Republic. -- 3: Aristotle's Theory of Justice. -- 4: From Nature to Artifice: Aristotle to Hobbes. -- 5: The Emergence of Utility. -- 6: Kant's Theory of Justice. -- 7: The Idea of Social Justice. -- 8: The Theory of Justice as Fairness. -- Epilogue: From Social Justice to Global Justice? -- Source Notes. -- Glossary of Names. -- Index.
Keywords: Justice (Philosophy) -- History; Social justice -- Philosophy